Electrolytes: In Situ Synthesis of a Hierarchical All‐Solid‐State Electrolyte Based on Nitrile Materials for High‐Performance Lithium‐Ion Batteries (Adv. Energy Mater. 15/2015). Issue 15 (August 2015) - Zhou, Dong; He, Yan‐Bing; Liu, Ruliang; Liu, Ming; Du, Hongda; Li, Baohua; Cai, Qiang; Yang, Quan‐Hong; Kang, Feiyu
<x xml:space="preserve">Abstract</x> In article number 1500353, Yan‐Bing He, Feiyu Kang, and co‐workers report the successful preparation of a hierarchical all‐solid‐state electrolyte based on nitrile materials via an in‐situ synthesis method. This electrolyte exhibits low flammability, excellent flexibility, and outstanding electrochemical performance, and has particular applications potential in wearable devices and electric vehicles.